2021
DOI: 10.3390/cancers13153662
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk of Long Bone Metastases: A Review of Current and New Decision-Making Tools for Prophylactic Surgery

Abstract: Long bone pathological fractures very much reflect bone metastases morbidity in many types of cancer. Bearing in mind that they not only compromise patient function but also survival, identifying impending fractures before the actual event is one of the main concerns for tumor boards. Indeed, timely prophylactic surgery has been demonstrated to increase patient quality of life as well as survival. However, early surgery for long bone metastases remains controversial as the current fracture risk assessment tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 116 publications
0
1
1
Order By: Relevance
“…Mosher et al [16] assessed outcomes in patients with pathologic fractures and found patients who sustained pathologic fractures were younger, female, had non-commercial insurance, increased blood transfusions, length of stay/hospitalization, total cost of care, and in-hospital mortality compared to patients who underwent prophylactic fixation for osseous metastases, similar to our results. Contrary to our study, literature has identified patients with breast cancer to be at increased risk of pathologic fracture, likely due to a prolonged survival time compared to other tumors [17] . We hypothesize our study did not observe an increased risk due to the increased proportion of breast cancer patients receiving antiresorptive therapy and possibly duration of follow-up.…”
Section: Factors Associated With Pathologic Fracture In Patients With...contrasting
confidence: 99%
“…Mosher et al [16] assessed outcomes in patients with pathologic fractures and found patients who sustained pathologic fractures were younger, female, had non-commercial insurance, increased blood transfusions, length of stay/hospitalization, total cost of care, and in-hospital mortality compared to patients who underwent prophylactic fixation for osseous metastases, similar to our results. Contrary to our study, literature has identified patients with breast cancer to be at increased risk of pathologic fracture, likely due to a prolonged survival time compared to other tumors [17] . We hypothesize our study did not observe an increased risk due to the increased proportion of breast cancer patients receiving antiresorptive therapy and possibly duration of follow-up.…”
Section: Factors Associated With Pathologic Fracture In Patients With...contrasting
confidence: 99%
“…Bone metastases lead to pain, hypercalcemia, and complications such as medullar compression and pathological fracture. Long bone pathological fractures are the most severe complications which have high mortality rates [ 22 ]. According to a study by Saad et al, Pathological fractures have been linked to significantly lower survival rates for breast cancer, multiple myeloma, and prostate cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the two cohorts, the discriminative ability of the radiomics nomogram was quantitatively measured using AUC, and the calibration curves were plotted based on observed probabilities and the nomogram-estimated probabilities ( 15 ). To evaluate the clinical utility of the radiomics nomogram, the decision curve analysis (DCA) was executed by calculating the net benefits at different threshold probabilities in the combined training and validation cohorts ( 16 ). The flowchart of this research is shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%